Menopausal symptoms in women and men aged 45-55 - Bielawska-Batorowicz, Eleonora (Menopause Review/Przegląd Menopauzalny, 2005)
Objective: There were two aims of the study: to look at menopausal symptoms in women and men of the same age, and to test whether menopausal women characterize their experiences in the same way when asked to describe their menopausal symptoms and when asked to describe their present well-being. Subjects and methods: The sample of 45-55 years old subjects included 109 women and 96 men. None of the participants received any form of hormonal treatment at the time of study. The 25-itmes Menopausal symptoms list ('Moje samopoczucie') was administered. This measure allowed to evaluate the prevalence of symptoms in the sample, and to describe frequency and intensity of symptoms. Results: All types of symptoms, including vasomotor symptoms, were reported by women and men. However, the mean number of symptoms was significantly lower for men. Women described their experiences in the same way despite the instruction pointing to menopausal transition or present well-being. Conclusion: Typical menopausal symptoms, including vasomotor symptoms, are not unique for women. They are also experienced by men, however less frequently and less intensively.